Health Education and Optimizing Balanced Nutrition for Student’s SDN 2 Sirnajaya Garut - Nurhabibah; Rosmini; Ilham Ahmad Nur Amal; Yunisa Tiara Sari; Neng Ratna Wulan; Delin Arlina; Siti Nurajijah; Dea Asgarita; Syaeful Hidayat; Novriyanti Lubis (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
To obtain balanced nutrition, the food consumed every day must contain various nutrients of the type and amount according to needs. In addition, it is necessary to consider a variety of foods, a clean lifestyle, physical activity, and weight monitoring. National data shows that Indonesian children with short stature reached 27,7% and obese children reached 9.2%. this indicates that many school-age children are still experiencing a nutritional crisis. The increasing rates of stunting and obesity are the result of unhealthy diets and lack of nutrition education. The counseling activity was located at SD Negeri 2 Sirnajaya Garut with the theme “Optimizing Balanced Nutrition”, carried out by the PKM team of Garut University pharmacy students and Padjajaran University pharmacy students. The activity aims to increase children’s understanding of the importance of balanced nutrition in supporting physical and cognitive growth. This activity involved 5th and 6th grade students with 43% male students and 57% female students. This activity includes a pretest, posttest, provision of educational materials delivered through presentations, educational videos, and distribution of flyers, and a question and answer session. Based on the results of the data obtained, this counseling succeeded in increasing student understanding from 67% to 78%, and students became aware of implementing a healthy lifestyle to obtain balanced nutrition.